The Impact of Negative Gossip in the Workplace and Workplace Ostracism on Prosocial Behavior in the Workplace: Mediation of Knowledge Hiding in Food MSMEs Worker’s - Elfia Nora; Sopiah Sopiah; Syihabudhin Syihabudhin (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Workplace gossip is a behavior that is now a common thing for some people, but it can have a negative impact if there is no control over workplace gossip behavior, it can cause social conflicts between workers and business owners. Research Objectives: (1) To test how Negative Workplace Gossip affects Knowledge hiding in Food MSME Workers, (2) to test how Workplace Ostracism affects Knowledge hiding in Food MSME workers, (3) to test how Knowledge hiding affects Prosocial Behavior on Food MSME workers, (4) to test how Negative Workplace Gossip affects Prosocial Behavior in Food MSME workers, (5) to test how Workplace Ostracism affects Prosocial behavior, (6) to test how Negative Workplace Gossip affects Prosocial Behavior through Knowledge hiding, (7) to test how Workplace Ostracism affects Prosocial Behavior through Knowledge hiding in Food MSME workers. This type of research is quantitative using a causality approach, with a sample of 74 BBJ food MSME workers. From the research conducted, the results were obtained (1) There is an effect of Negative Workplace Gossip on Knowledge hiding in Food MSME Workers, (2) There is an effect of workplace ostracism on knowledge hiding in Food MSME workers, (3) There is an effect of knowledge hiding on prosocial behavior in Food MSME workers, (4) There is an influence Negative Workplace Gossip on prosocial behavior in Food MSME workers, (5) There is an effect of Workplace Ostracism on prosocial behavior, (6) There is an effect of Negative Workplace Gossip on Prosocial Behavior through Knowledge hiding, (7) There is an effect of Workplace Ostracism on Prosocial Behavior through Knowledge hiding on Food MSME workers.